Performance analysis of two packet scheduling algorithms in downlink 3GPP LTE system - Xue, Minjie; Sandrasegaran, Kumbesan; Mohd. Ramli, Huda Adibah; Lin, Cheng-Chung (IEEE, 2010)
This paper evaluates the performance of two simple packet scheduling algorithms for real-time traffic in the third generation partnership project long term evolution (3GPP LTE) system. These algorithms, known as Algorithm 1 and Algorithm 2 for this paper, were proposed to support real-time traffic in orthogonal frequency division multiple access (OFDMA) system. Simulation results show that Algorithm 1 outperforms Algorithm 2 by achieving a lower packet delay and packet loss rate while having almost similar throughput and fairness performance compared to Algorithm 2.